Counselors’ Experiences with Infant and Young Child Feeding Tele-Counseling: A Phenomenological Study - Fajar Tri Waluyanti; Yeni Rustina; Hadiyati Fudla; Nani Nurhaeni; Jen-Jiaun Liaw; Insi Farisa Desy Arya; Milawati Milawati; Firda Dewi Yani (Jurnal Keperawatan Indonesia, 2022)
The global COVID-19 pandemic has influenced the intervention delivery of Indonesia’s stunting reduction program. In this context, e-counseling can be adapted as an innovative approach to deliver interventions. This study aimed to explore counselors’ experiences when conducting tele-counseling. The five participants in this phenomenological study were counselors who had received breastfeeding and infant and young child feeding (IYCF) counseling training and participated in counseling service activities. The participants were selected using a purposive sampling technique. In-depth interviews were conducted with each of the participant until data saturation was reached. Each interview was transcribed and analyzed using thematic analysis method. Four themes were found in this study: exciting experiences, essential counseling skills, privacy concerns, and tele-counseling as service solution. The recommendation derived from this study is to continue the IYCF tele-counseling program as a service solution at health facilities.   Abstrak Pengalaman Konselor Telekonseling Pemberian Makan Bayi dan Anak: Studi Fenomenologi. Pandemi global telah memengaruhi program penanggulangan stunting di Indonesia. Pendekatan e-konseling merupakan intervensi inovatif yang dapat diadaptasi dalam situasi ini. Penelitian ini bertujuan untuk mengeksplorasi pengalaman konselor saat melakukan telekonseling. Sebanyak lima partisipan adalah konselor yang pernah mengikuti pelatihan konseling menyusui, pelatihan konseling Pemberian Makan Bayi dan Anak (PMBA) serta melakukan kegiatan layanan konseling dalam program telekonseling PMBA. Partisipan dipilih dengan menggunakan teknik purposive sampling. Setiap partisipan mendapatkan sesi wawancara mendalam satu per satu hingga saturasi data tercapai. Setiap wawancara kemudian ditranskripsi dan dianalisis menggunakan metode analisis tematik. Ada empat tema yang ditemukan dalam penelitian ini, yaitu pengalaman yang menyenangkan, keterampilan konseling yang esensial, perhatian terhadap privasi, dan konseling jarak jauh sebagai solusi layanan kesehatan. Rekomendasi penelitian ini adalah melanjutkan program telekonseling sebagai solusi layanan di fasilitas kesehatan. Kata Kunci: fenomenologi, pandemi COVID-19, pengalaman konselor, telekonseling pemberian makan bayi dan anak